Cultural Dispositions of Haitian Mothers in the School Choice of Their Children in Chile; [Disposições Culturais de Mães Haitianas Na Escolha Escolar de Seus Filhos/As No Chile]; [Disposiciones Culturales de Madres Haitianas en la Elección Escolar de Sus Hijos/As en Chile] - Margarit-Segura, D; Cordoba-Calquin, C (Centro de Estudos Educacao e Sociedade - CEDES, 2023)
From a socio-structuralist theoretical approach, the concept of schooling habitus is proposed to analyze the way in which Haitian migrant families in Chile access and remain in schools in which they are segregated along with other migrant families. Through a qualitative device for analysis and data collection and from a case study and interviews with Haitian mothers with children in different schools in Santiago, it is concluded that such segregation is due to an interaction between the cultural dispositions of these families towards schooling together with the depopulation of certain types of Chilean schools due to objective factors. © 2023, Centro de Estudos Educacao e Sociedade - CEDES. All rights reserved.